Aplikasi pedagogiadic berbasis web sebagai sumber belajar masa pandemik covid-19 - Rudi Susilana; Gema Rullyana; Riche Cynthia Johan; Ardiansah Ardiansah (Jurnal Pendidikan dan Pengajaran, 2022)
The Information technology media that can quickly provide information about educational terms make it more difficult for people to learn. The absence of supporting media makes it increasingly difficult for people to learn terms and obtain information about the scientific language of terms quickly and accurately. This study aims to analyze the usability and ease of web-based pedagogiadic applications as learning resources. The research approach used is a quantitative approach with an explanatory survey method. The subjects in this study were students of the library and information science study program using web-based pedagogiadic applications with a total of 90 people. Data collection techniques used questionnaires, and data analysis techniques used path analysis. The results of the research being done were there are two things that affect the use of web-based pedagogiadic applications as learning resources. The perceived usefulness of web-based pedagogiadic applications provides benefits for themselves or individuals to use the application as a learning resource. Perceived ease of use, web-based pedagogiadic applications that are easy to use have an influence on individuals to use these applications in supporting teaching and learning activities.